Comparative Efficacy of Tonic Chinese Herbal Injections for Treating Sepsis or Septic Shock: A Systematic Review and Bayesian Network Meta-Analysis of Randomized Controlled Trials - Xiao, Lu; Niu, Liqing; Xu, Xinyi; Zhao, Yuetong; Yue, Linkai; Liu, Xinqiao; Li, Guiwei (Frontiers in Pharmacology, 2022)
Background: Sepsis has high mortality and is responsible for significant healthcare costs. Chinese herbal injections (CHIs) have been widely used in China as a novel and promising treatment option for sepsis. Therefore, this study assessed and ranked the effectiveness of CHIs to provide more sights for the selection of sepsis treatment. Method: Eight databases were searched from their inception up to September 1st, 2021. The methodological quality of included study was evaluated by the Revised Cochrane risk-of-bias tool for randomized trials. Then Bayesian network meta-analysis was performed by OpenBUGS 3.2.3 and STATA 14.0 software. The surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the examined treatments. Publication bias was reflected by a funnel plot. Results: A total of 50 eligible randomized controlled trials involving 3394 participants were identified for this analysis. Five CHIs including Shenfu injection, Shenmai injection, Shengmai injection, Shenqifuzheng injection, and Huangqi injection were included. The results of the NMA and sensitivity analysis showed that Shenqifuzheng (MD=-4.48, 95% CI=-5.59 to -3.24), Shenmai (MD=-3.38, 95% CI=-4.38 to -2.39), Shenfu (MD=-2.38, 95% CI=-3.03 to -1.70) and Shengmai (MD=-1.90, 95% CI=-3.47 to -0.31) combined with Western medicine (WM) had a superior effect in improving the APACHE II score. Based on SUCRA values, Shenqifuzheng injection (95.65%) ranked highest in the APACHE II score, followed by Shenmai (74%), Shenfu (47.1%), Shengmai (35.3%) and Huangqi injection (33.2%). Among the secondary outcomes, Shenmai injection was the most favorable intervention in reducing PCT and CRP levels, and Shenqifuzheng injection was the second favorable intervention in reducing CRP level. Shenfu injection combined with WM was more effective than the other treatments in decreasing the serum IL-6 and TNF-α levels and lowering the 28-day mortality. Regarding the improvement of immune function, Shenqifuzheng injections had obvious advantages. Conclusion: In conclusion, Shenqifuzheng injection was the optimum treatment regimen to improve APACHE II score, reduce CRP level, and regulate immune function. Shenfu injection was superior in reducing the expression of inflammatory factors and decreasing 28-day mortality. Nevertheless, more multicenter, diverse, and direct comparisons randomized controlled trials are needed to further confirm the results.